Comparative toxicity and distribution of InCl3 and In2O3 nanoparticles in rats. (1st October 2016) - Amiri, Asghar
Abstract: Recent studies have reported that metal oxide nanoparticles had potential adverse effects. In this research, the tissue distribution and toxic effects of administered InCl3 (bulk) and indium (III) oxide Nanoparticles (In2 O3 -NPs < 45 nm, BET of 43.6 m 2 /g and average hydrodynamic diameter of 79.97 nm) were investigated. Male Wistar rats were treated with a single intraperitoneal injection of InCl3 (bulk) and In2 O3 -NPs (2 mg/kg body weight, daily) for four consecutive weeks. Indium, copper and iron concentrations were measured by using ICP-OES. The indium levels were highest in the liver, followed in decreasing order by the levels in the spleen, kidney and intestine. The concentration of indium in In2 O3 -NPs exposed rats was more than InCl3 group and indium exposure caused significant decrease on Hb, RBC levels, PLT count and copper and iron concentrations in organs, which is probably due to an interference that could take place by indium (III) through iron (III) uptake mechanism.